2003
DOI: 10.1183/09031936.03.00001803
|View full text |Cite
|
Sign up to set email alerts
|

Induced sputum IL-8 gene expression, neutrophil influx and MMP-9 in allergic bronchopulmonary aspergillosis

Abstract: Allergic bronchopulmonary aspergillosis (ABPA) is a hypersensitivity reaction to the fungus Aspergillus fumigatus, causing severe asthma that may progress to bronchiectasis. Sputum neutrophilia can occur in association with sputum eosinophilia and correlates with the degree of bronchiectasis. The mechanisms of sputum neutrophilia in ABPA are not known. The aim of this study was to investigate the role of the chemokine interleukin (IL)-8 in sputum neutrophilia in ABPA.Induced sputum was obtained from subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 34 publications
1
36
0
2
Order By: Relevance
“…There is a robust correlation between airway neutrophils and human asthma (recently reviewed in Ref. 53): the severity of airway disease appears to correlate with number of neutrophils in the airway in both asthma (54) and allergic bronchopulmonary aspergillosis (8,25), and neutrophils are overrepresented in patients with asthma exacerbations, severe or poorly controlled asthma, and in those who die of asthma (9,11,(55)(56)(57)(58)(59)(60). In the context of this strong association noted in human disease, our study found long-term elevation in lung neutrophils in a mouse model of chronic airway allergy to clinically relevant Ags of a ubiquitous environmental mold.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a robust correlation between airway neutrophils and human asthma (recently reviewed in Ref. 53): the severity of airway disease appears to correlate with number of neutrophils in the airway in both asthma (54) and allergic bronchopulmonary aspergillosis (8,25), and neutrophils are overrepresented in patients with asthma exacerbations, severe or poorly controlled asthma, and in those who die of asthma (9,11,(55)(56)(57)(58)(59)(60). In the context of this strong association noted in human disease, our study found long-term elevation in lung neutrophils in a mouse model of chronic airway allergy to clinically relevant Ags of a ubiquitous environmental mold.…”
Section: Discussionmentioning
confidence: 99%
“…The association of neutrophil presence and MMP-9 activity is recognized in human airway allergy (25,70,71) and MMP-9 deficiency affects airway responses in mouse models of airway allergy (44 -47, 72, 73). Importantly, while our results underline the relevance of neutrophil-derived MMP-9 in airway inflammation, they do not preclude a role for other cellular sources of this enzyme in the context of allergy; indeed, our results indicate that MMP-9 activity in the lungs is substantially reduced, but not completely ablated, in the absence of neutrophils.…”
Section: Figure 10mentioning
confidence: 99%
See 1 more Smart Citation
“…The costimulatory molecule OX40 ligand has been found to be important in Th2 inflammatory responses in patients with ABPA associated with cystic fibrosis, with increased Th2 activity inversely correlating with circulating vitamin D levels (88). Proteolytic enzymes and mycotoxins from Aspergillus in colonized airways, along with eosinophilic inflammation and neutrophilic inflammation, may cause the characteristic central bronchiectasis seen in many cases of ABPA (50).…”
Section: Abpamentioning
confidence: 99%
“…Aspergillus fumigatus, which induces allergic bronchopulmonary aspergillosis (ABPA) in 25% of severe asthmatics, is one of the most common fungi involved (1,2). Neutrophilic airway inflammation is now well recognized as being a feature of severe asthma (3)(4)(5) and ABPA (6,7). During acute infection, neutrophils are crucial for antifungal defense (8,9), and lack of neutrophils is the best appreciated risk factor for invasive aspergillosis (10).…”
Section: Th17 | Tolerancementioning
confidence: 99%